TOGUSAKOV’S SCIENTIFIC ACTIVITY – SYSTEMICITY IN THE CONTEXT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the article, Togusakov’s creative activity is considered as a complete systemconsisting of three subsystems. The theory of the system, its origin and evolution, purpose andmethod of problem solving are described before me. Emphasis is placed on leadership andmanagement activities in the third subsystem of Togusakova’s work. Decomposition of thephilosophy of development in an independent country in the transition period is shown.
Keywords: system, internal, complex systems, transition period, decomposition, systematic analysis, scientific activity.